Regional Investment Policies Based on Local Potential to Strengthen a Sustainable Sharia Economy in South Kalimantan - Muhammad Hendri Yanova; Parman Komarudin; Ifrani; Muhammad Rifqi Hidayat; Muhamad Rahmani Abduh (Al-Hiwalah: Journal of Sharia Economic Law, 2026)
The urgency of this research lies in strengthening the role of investment by the Government of South Kalimantan Province as an instrument for both economic growth and equitable regional development. Normatively, such investment has been directed to generate economic and social benefits and to enhance public welfare, as stipulated in Article 2 paragraphs (1) and (2) and Article 3 letters (a) to (c) of Minister of Home Affairs Regulation No. 52 of 2012. However, it has not yet been fully integrated with the development of the Islamic economy, despite its significant potential in the region. This study employs a normative juridical method with statute approach and conceptual approach. The primary legal materials include regulations on regional government investment under Minister of Home Affairs Regulation No. 52 of 2012, provisions on regional capital participation within the local government legal framework, and regulations on regional investment incentives and facilities under Government Regulation No. 24 of 2019. These materials are analysed systematically through the lens of maqāṣid sharī‘ah. The results of this study indicate that regional investment policy should be directed as a selective instrument to promote both growth and equitable distribution through investments in sectors based on local potential, thereby increasing income and employment absorption, under the supervision of the regional head. Furthermore, regional investment policies can be sustainably integrated with Islamic principles by emphasising a maṣlaḥah-oriented approach.